Ship fuel consumption monitoring and fault detection via partial least squares and control charts of navigation data. (February 2019) - Capezza, C.; Coleman, S.; Lepore, A.; Palumbo, B.; Vitiello, L.
Highlights: EU regulation urges to monitor, report and verify ship harmful emissions. Modern statistical framework for fuel consumption monitoring is proposed. The framework has been applied to Ro-Ro Pax cruise ships. The framework supports emission saving verification and prognosis of faults. Abstract: New regulations in the shipping sector aim to give greater transparency to operations and public access to CO2 emissions data. EU regulation 2015/757 became mandatory in January 2018 and urges shipping companies to set up systems for daily monitoring, reporting and verification (MRV) of emissions for individual ships. Manual acquisition and handling of emissions data may be allowed (e.g. bunker fuel delivery note, bunker fuel tank monitoring), but is adversely affected by uncertainty due to human intervention and will eventually be unusable for monitoring purposes. However, the massive amounts of navigation data acquired by multi-sensor systems installed on-board of modern ships have great potential to aid compliance with regulations but their use is hampered by the lack of effective analytical methods in the maritime literature. This work demonstrates a statistical framework and automatic reporting system for fuel consumption monitoring that addresses the MRV requirements needed to comply with the regulations. The framework has been applied to the Grimaldi Group's Ro-Ro Pax cruise ships and is shown, in addition, to be capable of supporting fault detection as well as verifying CO2 savings achieved after energy efficiency initiatives.